Government Guidelines to Transform the Online Shopping Experience for Customers - Muhammad Younus; Achmad Nurmandi; Suswanta; Ibrahim Shah (Westscience Press, 2023)
Digital Transformation and Innovation are always essential parts of continuous growth in any field and business, through which any business model can adjust and adapt to the ever-changing world. E-Commerce is also one example of it, which in the past decade has been a smart way because of the online shopping experience, but after covid-19, its importance has increased even more. That is why we believe that in order to make E-Commerce relevant in the future, it is crucial to make innovations in it to transform it according to the customer requirement. So, This Article will give guidelines and direction from the government end to Private Sector in order to change the dynamics of Online Shopping and make it adaptable according to future technological advancement and expectations through different ideas that we will be going to discuss here. We will clarify through findings here that it is vital to emphasize now, and planning for it accordingly will provide ease and an advantage over others in the future. We attempted to map out each stage of online and offline purchasing in order to detect any gaps that may currently exist. The causes of the gaps were uncovered, and eventually, ways to automate the process and incorporate it into the online shopping experience were discovered, which we will discuss in detail in paper. As a result, the key to this study is government research, which is then implemented as recommendations to the private sector to continue improving the online shopping experience.